Temporal Variation Analysis From Troposphere Delay Using GPS (Study: Bandung, Indonesia) - Pradipta, Dhota; Kuntjoro, Wedyanto; Prijatna, Kosasih (Indonesian Journal of Geospatial, 2012)
Abstract.Tropospheric delay is the amount of distortion caused by the deceleration of satelliteâs signal propagation due to the influence of troposphere. The value of this delay is certain effect of elevation angle that is called the slant delay. In the processing of GPS signals correction, the value of slant delay will be converted using a mapping function to the measured value of the zenith delay which became known as the Zenith Total Delya (ZTD). Zenith value is an accumulated value of the tropospheric delay along the signalâs path at the zenith direction.Â The value of ZTD can be determined by GPS technique. In Geodesy, ZTD is a nuisance parameter, but for meteorology, it is a parameter of interest, which causes from variability of the atmospheric constituens. The section of ZTD, i.e. Zenith Wet Delay (ZWD), could be derived by substracting Zenith hydrostatic Delay (ZHD) component from ZTD. By surface temperature readings at the GPS receiver, the retrieved ZWD can then be transformed with additional uncertainty into an estimate of the Precipitable Water Vapor (PWV).Â The aim of this research is to study temporal behavior of PWV at ITB campus, as it is revealed from GPS measurements. According to the research that has been conducted, we obtained some results, i.e. The data quality and strategy which were used in processing could affect the result, In particular, we found that, within 20 minutes, maximum and minimum PWV values could reach 85.2 mmand 6.4 mm, respectively. It may indicate that the atmosphere above the studied are varies highly. Temporal condition in observation point that appears in result such as at 12.00 â 18.00 WIB often shows significant irregular anomalies of PWV that influenced local area observation.Â Keywords: GPS, PWV, temporal analysis, ZTD.Â